Every deadly suspicion - Cantore, Janice (Tyndale House Publishers, 2025)
In Dry Oaks, California, Chief of Police Hanna Keyes has long believed her father, Joe, is a murderer, justly imprisoned. When she's told he's dying and is being given compassionate release from prison, she wants nothing to do with him. But taking him in might be Hanna's one shot at cracking the cold case, so she reluctantly agrees to oversee his care. Joe's arrival in Dry Oaks seems to set off a chain reaction of crimes. Then an infamous true-crime podcaster comes sniffing for information, and Hanna's first love, Jared, shows up just when she least needs the distraction. As Hanna tries to convince Joe to reveal what he knows about the missing persons, evidence in the cold case surfaces at a suspiciously rapid pace... suggesting there's more to the murders than people thought. With Joe's strength failing, Hanna and her colleagues look for answers, not only about the past but also about recent criminal dealings in Dry Oaks. As the puzzle pieces start to fit together, it becomes clear that there's a sinister plot at work, far more wide-reaching than anyone suspected, and that someone is desperate to silence the truth at any cost. --